GeNeDis 2016 : genetics and neurodegeneration - Vlamos, Panayiotis (Springer, 2017)
The 2nd World Congress on Genetics, Geriatrics and Neurodegenerative Disease Research (GeNeDis 2016), will focus on recent advances in geriatrics and neurodegeneration, ranging from basic science to clinical and pharmaceutical developments and will provide an international focum for the latest scientific discoveries, medical practices, and care initiatives. Advances information technologies will be discussed along with their implications for various research, implementation, and policy concerns. In addition, the conference will address European and global issues in the funding of long-term care and medico-social policies regarding elderly people. GeNeDis 2016 takes place in Sparta, Greece, 20-23 October, 2016. This volume focuses on the sessions that address neurodegenerative diseases.
Keywords: Nervous system -- Degeneration -- Congresses.; Genes -- Congresses.; elektronické knihy; electronic books